Nature and significance of intraspecific variation in the early Cambrian oryctocephalid trilobite Oryctocephalites palmeri Sundberg and McCollum, 1997. (January 2020) - Webster, Mark; Sundberg, Frederick A.
Abstract: Oryctocephalid trilobites are seldom abundant and often tectonically deformed, creating problems for robust species delimitation and compromising their utility in biostratigraphic and evolutionary studies. By studying more than 140 specimens recovered from the upper portion of the Combined Metals Member (Pioche Formation, Nevada; Cambrian Stage 4, Series 2), we exploit a rare opportunity to explore how morphological variation among oryctocephalid specimens is partitioned into intraspecific variation versus interspecific disparity. Qualitative and quantitative analyses reveal that two species are represented: Oryctocephalites palmeri Sundberg and McCollum, 1997 and Oryctocephalites sp. A, the latter known from a single cranidium stratigraphically below all occurrences of the former. In contrast to the conclusions of a previous study, there is no evidence of cranidial dimorphism in O. palmeri . However, that species exhibits considerable variation in cranidial shape and pygidial spine arrangement and number. Cranidial shape variation within O. palmeri is approximately one-half of the among-species disparity within the genus. Comparison of cranidial shape between noncompacted and compacted samples reveals that compaction causes significant change in mean shape and an increase in shape variation; such changes are interpretable in terms of observed fracture patterns. Nontaphonomic variation is partitioned into ontogenetic and nonallometric components. Those components share similar structure with each other and with interspecific disparity, suggesting that ontogenetic shape change might be an important source of variation available for selection. This highlights the importance of ontogenetic and taphonomic sources of variation with respect to species delimitation, morphospace occupation, and investigation of evolutionary patterns and processes.